2018
DOI: 10.15548/jt.v25i3.485
|View full text |Cite
|
Sign up to set email alerts
|

The Intervention of Using Reciprocal Teaching Technique and Learning Styles on Students’ Reading Comprehension

Abstract: Reading is one of language skills that should be acquired by the students who learn English course in junior high school level. In learning a foreign language, students face many problems, especially in comprehending reading text. In reading process, the students have to understand the meaning of the text through their learning styles and combining their background knowledge, experiences, and situation with the information which is stated on the text. This article was to investigate the empirical evidence on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There are some differences between them as well. In the reciprocal teaching method without reflection, Egiyantinah et al (2018) found that the reciprocal teaching method is effective for improving reading comprehension; however, students' learning styles should be considered in order to gain more effectiveness. Regarding the RBRT approach, the teachers not only used reciprocal teaching alone but also reflected on their instructional context.…”
Section: Discussionmentioning
confidence: 99%
“…There are some differences between them as well. In the reciprocal teaching method without reflection, Egiyantinah et al (2018) found that the reciprocal teaching method is effective for improving reading comprehension; however, students' learning styles should be considered in order to gain more effectiveness. Regarding the RBRT approach, the teachers not only used reciprocal teaching alone but also reflected on their instructional context.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, teachers employ various instructional strategies to help students effectively comprehend reading texts. There were also some studies investigating teachers’ instructional strategies on students’ reading comprehension; for example, Egiyantinah et al.’s (2018) study investigating the effect of the reciprocal teaching strategy and learning styles on students’ reading comprehension achievement; Anyiendah et al.’s (2019) study exploring the effect of the interactive approach on learners’ achievement in reading comprehension in Vihiga, Kenya; Ahmada’s (2019) study examining the effect of the jigsaw learning model in teaching reading comprehension on narrative text; Salari and Hosseini’s (2019) study scrutinizing the effect of the team-based learning strategy on the Iranian intermediate EFL students’ reading comprehension achievement from the Golrizan Language Institute in Mashhad, Iran; and Barua’s (2021) study inquiring into the effect of the paraphrasing strategy on the tertiary level students’ reading comprehension achievement from the Gauhati University, India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, teaching reading comprehension is of great importance for teachers to help students' complete understanding of the reading text. Egiyantinah et al (2018) also highlighted the teaching technique as one of the most important factors which determine the success or the failure of students' reading comprehension process. In teaching reading comprehension, it is a complex interaction between a teacher's instructional strategy, setting, readers' background, readers themselves, task, and the reading text itself (Yukselir, 2014).…”
Section: Conceptualization To Teaching Reading Comprehensionmentioning
confidence: 99%
“…RH1: The pre-and post-tests aimed for this sub-study are expected to be reliable and valid for measuring students' reading comprehension achievement (Egiyantinah et al, 2018).…”
Section: Research Questions (Rq1 -Rq3)mentioning
confidence: 99%